2020
DOI: 10.1155/2020/7973568
|View full text |Cite
|
Sign up to set email alerts
|

JAK3 and TYK2 Serve as Prognostic Biomarkers and Are Associated with Immune Infiltration in Stomach Adenocarcinoma

Abstract: Background. Stomach adenocarcinoma (STAD) is one of the most common malignant tumors. The Janus kinases (JAKs) play a significant part in cellular biological process, inflammation, and immunity. The roles of JAKs in STAD are still not systematically described. Methods. A series of bioinformatics tools were used to clarify the role of JAKs in STAD. Results. JAK3/TYK2 levels were significantly increased in STAD during subgroup analyses based on gender, tumor grade, cancer stages, and nodal metastasis status. STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This analysis provides preliminary data on the role of ARID1A in CTL infiltration. To learn more about the effects of ARID1A on immunological infiltration, we evaluated previously described biomarkers of major immune cell types ( 15 , 26 ) and their association with ARID1A levels ( Table 1 ). Reportedly, the immunoinhibitory molecules attach to the PD-1 receptor on the surface of CD8+ T cells to stop their function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis provides preliminary data on the role of ARID1A in CTL infiltration. To learn more about the effects of ARID1A on immunological infiltration, we evaluated previously described biomarkers of major immune cell types ( 15 , 26 ) and their association with ARID1A levels ( Table 1 ). Reportedly, the immunoinhibitory molecules attach to the PD-1 receptor on the surface of CD8+ T cells to stop their function.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the immunoinhibitory molecules attach to the PD-1 receptor on the surface of CD8+ T cells to stop their function. Hence these molecules view immunotherapy resistance as the primary cause ( 15 ). While ARID1A deficiency enhanced PDL-1 expression ( 24 ), the findings of this study generally validated prior research in this field and proved that ARID1A deletion may influence immunity-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic phosphotyrosine peptide enrichment and quantitative mass spectrometry identified several activated kinases, including TYK2 (Y 292 ) and its downstream target signal transducer and activator of transcription 3 (STAT3) (Y 705 ), in metastatic castration-resistant prostate cancer [13]. In addition, RNA sequencing (RNA-seq) of the transcriptome revealed that TYK2 and JAK3 mRNA levels were significantly increased in stomach adenocarcinoma, and both proteins were found to be prognostic biomarkers [14]. Genomic screens have also implicated TYK2 as a pro-survival gene in soft-tissue sarcomas (Table 1).…”
Section: Tyk2 In Carcinomas and Sarcomasmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is a pre-programmed process by which polarized epithelial cancer cells de-differentiate into stem cells that can migrate and invade, [18,20,41,106,108,109] while stimulating proliferation [20,41,106,108,113], migration, invasion [113][114][115][116][117][118], and resistance to chemotherapy [107]. These functions of TYK2 lead to increased tumor aggressiveness and metastasis [14,20,22,36,106], resulting in greater patient mortality. Arrows (↑ or ↓) indicate direction of gene expression or protein activation change.…”
Section: Role Of Tyk2 In Metastasismentioning
confidence: 99%
See 1 more Smart Citation